Composting as a Holistic Approach for Food and Yard Waste Management in attaining Sustainable Organizations - Senadheera, W.H.M.D.P.; Chandith, P. (Faculty of Management Sciences, University of Sri Jayewardenepura, 2020)
Growth of the population and high urbanization in the world is presently escalating at a rapid rate per year and anthropological activities cause severe environmental degradation such as pollution of air, water, soil, deforestation etc. Humans generate huge quantities of trash in office buildings, schools, stores, hotels, restaurants and other commercial and institutional buildings and mostly it ends up in landfills. Landfills result in methane generation which can be contributed to the greenhouse effect. After breaking down of waste in landfills, leachate is toxic and can pollute groundwater, waterways and soil. There are about 40% of organic wastes in solid waste and significant portion of the budget is spent for waste management in many organizations, institutes etc. This paper aim to identify innovative techniques that can be used to speed up the process of composting in sustainable waste management in organization premises. The paper also identify potential application different composting practices especially in urban waste management to attain number of benefits such as save money, enhance sustainability, reduce greenhouse gas emissions, conserve resources etc. Furthermore, many organizations can simply establish a compost system for remove trash by using low technology, low cost techniques. It is hoped that the paper has provided a useful guide, not only for wastes management, but also for adding value to them.
Keywords: Composting, Methods and benefits, Sustainable organizations, Waste management.